Service Composition and Execution Plan Generation of Composite Semantic WEB Services Using Abductive Event Calculus. (27th December 2015) - Paulraj, D.; Swamynathan, S.; Chandran, Daniel; Balasubadra, K.; Prem, M. Vigilson
Abstract : Web Service composition is indispensable, as a single web service cannot satisfy the complex functional requirement of a user. The two key challenges of semantic web service composition are the discovery of the most relevant atomic services from the composite semantic web services and by no means we can assure the execution of the composed atomic services in a proper order. In this work, these two challenges are addressed, and a novel architecture is proposed for atomic service discovery, composition and automatic plan generation for the proper execution of its candidate services. The proposed architecture takes the advantage of abductive event calculus that uses abductive theorem prover to generate a plan for the proper order of execution of the atomic services. The research has found that the plan generated by the proposed architecture is sound and complete.